Accuracy of the small field dosimetry using Acuros XB and AAA dose calculation algorithms of eclipse treatment planning system within and beyond heterogeneous media for Trubeam 2.0 unit. (September 2016) - Codel, G.; Serin, E.; Cebe, M.S.; Mabhouti, H.; Pacaci, P.; Sanli, E.; Doyuran, M.; Kucukmorkoc, E.; Altinok, A.; Canoglu, D.; Kucuk, N.; Acar, H.; et al.
Abstract : Purpose: In this study, the comparison of dosimetric accuracy of Acuros XB and AAA algorithms were investigated for small radiation fields incident on homogeneous and heterogeneous geometries. Methods: Small open fields of Truebeam 2.0 Unit 1 × 1.2 × 2.3 × 3.4 × 4 cm 2 were used for this study. The fields were incident on homogeneous phantom and phantom containing lung, air, and bone inhomogeneities. Using the same film batch, the net OD to dose calibration curve was obtained using Trubeam 2.0 for 6 MV, 6 FFF, 10 MV, 10 FFF, 15 MV energies by delivering 0–800 cGy. Films were scanned 48 h after irradiation using an Epson 1000XL flatbed scanner. The dosimetric accuracy of Acuros XB and AAA algorithms in the presence of the inhomogeneities was compared against EBT3 film dosimetry Results: Open field tests in a homogeneous phantom showed good agreement between two algorithms and measurement. For Acuros XB, the minimum gamma analysis passing rates between measured and calculated dose distributions were 99.3% and 98.1% for homogeneous and inhomogeneous fields in the case of lung and bone respectively. For AAA, the minimum gamma analysis passing rates were 99.1% and 96.5% for homogeneous and inhomogeneous fields respectively for all used energies and field sizes. In the case of the air heterogeneity, the differences were larger for both calculations algorithms. Overall, when compared to measurement, the AcurosXB had better agreement than AAA. Conclusions: The Acuros XB calculation algorithm in the Eclipse TPS is an improvement over the existing AAA algorithm. Dose discrepancies were observed for in the presence of air inhomogeneities.